Land use and terrestrial arthropods at the Colombian Pacific coast - Löhr, Bernhard; Narváez, Alexandra (Revista Colombiana de Entomología, 2021)
Diversity, permanence, and activity of terrestrial arthropods were investigated in four areas of different land use in the lowlands of the Pacific coast of Colombia with the aim to identify potential predator species for the palm root borer, Sagalassa valida. Ten pitfall traps were established along a 100 m transect in four areas: a secondary forest, a 20 year.-old peach palm plantation, and two hybrid oil palm plantations of three and seven years of age, respectively. Twenty-two collections were made covering a whole year. All ants were identified to species or morphospecies level, the other arthropods to order or where possible to family level. In total, 50,603 arthropods were captured, the most abundant were ants (37.0 %), followed by Collembola (35.4 %), Acari (10.6 %), Coleoptera (7.0 %) and Diptera, Hemiptera and Araneae in almost equal numbers (around 2.5 %). Orthoptera (92 % Gryllidae) were present in all collections, always at low numbers. The highest number of ants were recorded in the oil palm transects; Diptera, Hemiptera and Orthoptera were more numerous in the secondary forest, Acari, Araneae and Collembola in the palm transects. Ectatomma ruidum was by far the dominant ant species (84.9 % of all specimens) and absent from only 20 of the 880 captures. The second most frequent ant genus were army ants with two species, Labidus praedator and L. coecus. Rainfall, even area-wide flooding, and temperature did not explain variability in captures of any taxonomic group satisfactorily. We conclude that E. ruidum might be the predator to provide control of the root borer and recommend further studies on its efficiency.